Lifestyle factors and health outcomes associated with infertility in women: A case-control study using National Health Insurance Database - Boyoung Jeon; Taeuk Kang; Sung Wook Choi (Reproductive Health)
Abstract Background Approximately one in six people is experiencing infertility at some point in their lives. In response, health insurance coverage for infertility treatments has been strengthened. However, studies examining lifestyle factors that affect infertility remain lacking, highlighting the need to generate objective evidence to address infertility issues using national-level datasets. Methods The General Healthcare Screening Program dataset from National Health Insurance Service database was employed in this study to examine infertility and childbirth among women aged 22–49 years. In 2020, 25,333 women with infertility and 73,759 women who had given birth were initially identified. After applying propensity score matching for age, Charlson Comorbidity Index score, and income level, the final study population included 24,325 women with infertility and 24,325 women who with childbirth. Employing a case–control study design, lifestyle factors (drinking, smoking, and physical activity) and health checkup outcomes (underweight, overweight, hypertension, diabetes, kidney function, anemia, and menstrual disorders) were assessed in this study. Statistical analyses included chi-squared tests, t-tests, and logistic regression. Results This study revealed significant risk factors for infertility: two high-risk lifestyle factors, including heavy drinking and smoking, and five health conditions, comprising underweight, hypertension, diabetes, kidney function loss, and menstrual disorders. Conversely, being overweight, not engaging in vigorous physical activity, and anemia were negatively associated with infertility. Conclusions These findings underscore the need for lifestyle modifications and personalized preconception care to improve fertility outcomes. Trial registration Not available.